Pengaruh Kadar Air dan Persamaan Model Bet untuk Prediksi Masa Simpan Kakao (Theobroma cacao L.) - Rita Hayati (Jurnal Teknologi dan Industri Pertanian Indonesia, 2017)
Effect of moisture content and BET equation to the shelf life of cocoa (Theobroma cacao L.) has been conducted. Increasing the quality of cocoa beans is with proper post-harvest handling, including how the harvest, the level of ripeness, curing, fermenting, drying up storage. The purpose of this study was to determine the water content and the appropriate levels of critical in determining the shelf life of cocoa. The benefits of this research are as information for farmers in determining the shelf life of cocoa in order to design a storage area corresponding to the respiratory system owned by cocoa. The results showed that the effect of fermentation facilitator (Staphilococcus cerevisiae) and drying temperature on water content showed that the fermentation facilitator (Staphilococcus cerevisiae) highly significant effect on water content. The drying temperature is also highly significant effect on water content. BET equation obtained was Y = 2,912x + 1.238 (R2 = 0.965), Y = 2,897x + 1.353 (R2 = 0.968) and Y = 2,806x + 1.89 (R2 = 0.954).